2017
DOI: 10.24843/spj.2017.v05.i03.p04
|View full text |Cite
|
Sign up to set email alerts
|

Mulligan Bent Leg Raise Lebih Meningkatkan Lingkup Gerak Sendi Lumbosakral Dan Menurunkan Disabilitas Dibandingkan Dengan Slump Stretching Pada Pengrajin Genteng Dengan Mechanical Low Back Pain Di Desa Darmasaba

Abstract: Background: Mechanical low back pain is pain that resulting from poor posture which cause decreased disability and limitation of lumbar range of motion. Purpose: The purpose of this study was to prove mulligan bent leg raise more effective to increase lumbosacral range of motion and decreased disability than slump stretching among tile craftsman with Mechanical low back pain in Darmasaba village. Methods: This research was an experimental study with pre and post test control group design. Sample of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Based on the initial assessment carried out by the community service team, there were many complaints of low back pain that occurred among roof tile craftsmen. This is also confirmed by research conducted by Prianthara et al (2017) which stated that roof tile craftsmen in Darmasaba Village experienced many complaints of low back pain. Complaints of low back pain can be caused by poor positioning when carrying out lifting and carrying activities in the roof tile making process.…”
Section: Implementation Of Work Attitude Bussiness Management and Pro...supporting
confidence: 68%
See 2 more Smart Citations
“…Based on the initial assessment carried out by the community service team, there were many complaints of low back pain that occurred among roof tile craftsmen. This is also confirmed by research conducted by Prianthara et al (2017) which stated that roof tile craftsmen in Darmasaba Village experienced many complaints of low back pain. Complaints of low back pain can be caused by poor positioning when carrying out lifting and carrying activities in the roof tile making process.…”
Section: Implementation Of Work Attitude Bussiness Management and Pro...supporting
confidence: 68%
“…If not addressed, it can result in musculoskeletal complaints which can reduce work performance. Previous research conducted by Prianthara et al (2017) revealed that the average roof tile craftsman in Darmasaba Village experienced complaints of lower back pain caused by work attitudes and continuous repetition of movements that were less ergonomic. The process of roof tile craftsmen for target partners can be seen in the Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results are also supported by Prianthara et al (2017) entitled "Mulligan Bent Leg Raise Increases the Range of Motion of the Lumbosacral Joint and Reduces Disability Compared to Slump Stretching in Tile Craftsmen with Mechanical Low Back Pain in Darmasaba Village" proving that Mulligan Bent Leg Raise causes posterior pelvic tilt which can improve the biomechanical function of the spine and pelvic so that lumbopelvic movement is not disturbed so that the range of motion of the joints increases.This research is also in line with research conducted by Wibawa et al (2018) which reported that there was a decrease in functional pain scores of 12.86 (SB 2.797) in sufferers of low back pain after administering ultrasound and Mc. Kenzie exercises.…”
Section: Resultsmentioning
confidence: 56%